Optimization of triethylene glycol dehydration of natural gas. (November 2019) - Chebbi, Rachid; Qasim, Muhammad; Abdel Jabbar, Nabil
Abstract: Dehydration using triethylene glycol (TEG) is widely used in natural gas processing to avoid corrosion and plugging of the flow lines. Optimization using Aspen HYSYS simulator and optimizer tool was performed to minimize the processing cost considering different sets of parameters: TEG circulation rate, numbers of theoretical trays (in the absorber and the stripping gas column), feed gas pressure and temperature, gas flow rate, gas price level and stripping gas rate. In addition to typical dew point depression simulation results reported in other publications, the present investigation also provides the minimum processing cost including both utilities and capital cost. The results based on the parametric optimization study yield criteria for design and optimum operating conditions for the dehydration process.